Impact of sex and role of coronary artery disease in out-of-hospital cardiac arrest presenting with refractory ventricular arrhythmias - Caputo, Maria Luce; Baldi, Enrico; Krüll, Joel Daniel; Pongan, Damiano; Cresta, Ruggero; Benvenuti, Claudio; Cianella, Roberto; Primi, Roberto; Currao, Alessia; Bendotti, Sara; Compagnoni, Sara; Gentile, Francesca Romana; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction There are limited data on sex-related differences in out-of hospital cardiac arrests (OHCAs) with refractory ventricular arrhythmias (VA) and, in particular, about their relationship with cardiovascular risk profile and severity of coronary artery disease (CAD). Purpose Aim of this study was to characterize sex-related differences in clinical presentation, cardiovascular risk profile, CAD prevalence, and outcome in OHCA victims presenting with refractory VA. Methods All OHCAs with shockable rhythm that occurred between 2015 and 2019 in the province of Pavia (Italy) and in the Canton Ticino (Switzerland) were included. Results Out of 680 OHCAs with first shockable rhythm, 216 (33%) had a refractory VA. OHCA patients with refractory VA were younger and more often male. Males with refractory VA had more often a history of CAD (37% vs. 21%, p 0.03). In females, refractory VA were less frequent (M : F ratio 5 : 1) and no significant differences in cardiovascular risk factor prevalence or clinical presentation were observed. Male patients with refractory VA had a significantly lower survival at hospital admission and at 30 days as compared to males without refractory VA (45% vs. 64%, p < 0.001 and 24% vs. 49%, p < 0.001, respectively). Whereas in females, no significant survival difference was observed. Conclusions In OHCA patients presenting with refractory VA the prognosis was significantly poorer for male patients. The refractoriness of arrhythmic events in the male population was probably due to a more complex cardiovascular profile and in particular due to a pre-existing CAD. In females, OHCA with refractory VA were less frequent and no correlation with a specific cardiovascular risk profile was observed.